A Comparative Evaluation of Ischemic Mitral Regurgitation in AMI Patients Managed by Revascularization Vs Optimal Medical Therapy - Saha, Jayanta; Singh, Sudhakar; Roy, Arnab; Bhargawa, Manoj (Asian Journal of Medical Sciences, 2019)
Objectives: Ischemic mitral regurgitation (IMR) is one of the frequent complications associated with coronary artery disease (CAD); but the optimal management of IMR is controversial. Our aim was to evaluate and compare the impact of medical therapy versus revascularization on the degree of MR. Methods: We performed observational follow up study on 114 patients admitted to our hospital with AMI and mild to moderate degree of MR. Multiple parameters were used to assess the severity of MR at baseline and after 1 year of follow up to assess the change in MR severity after medial therapy and revascularization. Results: In the medically managed group, MR grade improved in 28.57% of patients while 53.57% patients remained in the same grade as before. The grade of MR deteriorated from moderate to severe in 17.86% patients during follow up. In revascularization group; improvement in MR grade was observed in 60.71% of patients while 32.14% patients remained in the previous grade. Deterioration from moderate to severe occurred in 7.14% of patients. PCI and CABG subgroup analysis showed almost similar impact on degree of MR during follow up. Conclusion: From our study we concluded that revascularization; either in form of PCI or CABG, is associated with improvement in degree of MR when compared to optimal medical therapy alone.